Morphometric analysis of leaf indumentum distinguishes greyish oak (Quercus pedunculiflora K. Koch) and pedunculate oak (Quercus robur L.) across their Central-Eastern European range - Hegedüs Ivett; Sramkó Gábor; Bartha Dénes (Central European Forestry Journal)
White oaks are keystone species in European lowland forests. The micro-morphology of pedunculate oak (Quercus robur L.) and greyish oak (Quercus pedunculiflora K. Koch), two closely related taxa sometimes treated as subspecies, was compared in the present paper. Greyish oak – distributed in the Balkans and Asia Minor – is proposed as a climate-resilient substitute for Q. robur L. under intensifying droughts. For our study, we collected leaf samples from populations in Hungary, Romania and Bulgaria, and compared them using indumentum characteristics, focusing on trichome types as potential diagnostic markers for forestry practice. Morphological observations of trichome rays collected at standardised sampling plots were compared using either classical statistics (countable measurements) or morphological classification (trichome types). Three trichome types were present on greyish oak: glandular and simple-uniseriate, stellate, and fasciculate trichomes, whereas pedunculate oak predominantly displayed simple-uniseriate trichomes, except for one intermediate individual. On average, the simple-uniseriate trichome rays on the leaf epidermis of Q. pedunculiflora K. Koch measured 79.81 µm in length, while the same in Q. robur L. were found to be 67.41 µm; a difference that was statistically significant. Fasciculate trichomes (mean length 274.99 µm) were diagnostic for Q. pedunculiflora K. Koch, despite occasional stellate trichomes in transitional forms (mean length 149.55 µm). These results confirm robust micromorphological differentiation between the taxa, validating trichome traits as reliable identification tool. The denser indumentum of greyish oak may reflect drought adaptation, highlighting its potential for assisted gene-flow in climate-smart forestry. The clear morphological difference in leaf indumentum can help practicing foresters to distinguish between the two oaks.